Spraying of calcium carbonate nanoparticles in pineapple fruit reduces sunburn damages - Teixeira, Gelza Carliane Marques [UNESP]; Junior, José Sidnaldo Pinsetta [UNESP]; Mattiuz, Ben-Hur [UNESP]; Prado, Renato de Mello [UNESP]; Corrêa, Ana Júlia [UNESP]; Rocha, Antonio Márcio Souza [UNESP]; do Vale, Diego Wyllyam (Elsevier, 2022)
This study aimed to evaluate the effect of different concentrations of calcium carbonate nanoparticles preharvest sprayed on pineapple fruit. The treatments consisted of five concentrations of calcium carbonate nanoparticles: 0, 12.5, 25, 50, 100, and 200 g ha−1. The quality parameters were analyzed: soluble solids content (SSC), titratable acidity (TA), ratio (SSC/TA), ascorbic acid content, and firmness; also, colorimetric parameters on fruit pulp and peel: lightness (L*), coordinates a* and b*, chroma, hue angle, and yellowing index. The spraying of calcium carbonate nanoparticles reduced the damage caused by sunburn, increasing fruit quality. This effect was evidenced in fruit color by the increased L*, higher Hue angles, and lower yellowing index in the peel and pulp. In addition, we observed increased firmness, SSC/TA, and ascorbic acid in the pulp. Thus, it maintained quality characteristics and fruit color. This study proposes two calcium carbonate nanoparticles spraying during pineapple cultivation to control fruit sunburn, especially in tropical regions, guaranteeing high-quality fruit production and extending its postharvest commercialization.
Keywords: Ananas comosus (L.) Merril; Fruit quality; Fruit sunburn; Nanotechnology; Photoprotection